The joint impact of stock market and corruption on economic growth and development in Nigeria: evidence from cointegration and VECM analysis - Nageri, Kamaldeen Ibraheem; Nageri, Sherifdeen Ibraheem; Amin, Abdullateef (Serbian Journal of Management, 2015)
This paper studies the effect of capital market on economic growth in the presence of corruption in the Nigerian context. We employed the use of cointegration and Vector Error Correction Model (VECM). We find out that both corruption and capital market has long run associationship with economic development in Nigeria but has no short run relationship. This simply means that there is short run gain and long run pain for the Nigerian economy if corruption and capital market are not checked and well regulated respectively in Nigeria. We therefore recommend that government should strengthen the anti-graft agencies and equip them technologically and make them independent, educate the public on the problems associated with corrupt practices and the economic implication especially through the capital market and encourage local investors to invest in the capital market to improve liquidity and profitability of the Nigerian capital market.